Animal Models of Colitis-Associated Carcinogenesis. (12th January 2011) - Kanneganti, Manasa; Mino-Kenudson, Mari; Mizoguchi, Emiko
Abstract : Inflammatory bowel disease (IBD) is a group of chronic inflammatory disorders that affect individuals throughout life. Although the etiology and pathogenesis of IBD are largely unknown, studies with animal models of colitis indicate that dysregulation of host/microbial interactions are requisite for the development of IBD. Patients with long-standing IBD have an increased risk for developing colitis-associated cancer (CAC), especially 10 years after the initial diagnosis of colitis, although the absolute number of CAC cases is relatively small. The cancer risk seems to be not directly related to disease activity, but is related to disease duration/extent, complication of primary sclerosing cholangitis, and family history of colon cancer. In particular, high levels and continuous production of inflammatory mediators, including cytokines and chemokines, by colonic epithelial cells (CECs) and immune cells in lamina propria may be strongly associated with the pathogenesis of CAC. In this article, we have summarized animal models of CAC and have reviewed the cellular and molecular mechanisms underlining the development of carcinogenic changes in CECs secondary to the chronic inflammatory conditions in the intestine. It may provide us some clues in developing a new class of therapeutic agents for the treatment of IBD and CAC in the near future.